A feasibility study on the establishment of a library in the Doctor Jorge P. Royeca Hospital - Pascual, CD Nigel Reinerio M.; Santos, Mark Anthony A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
The issue about the Dr. Jorge P. Royeca Hospital (DJPRH) is that despite being a public hospital, it lacks a library that is supposed to cater to the information needs of the health care professionals that serve in the hospital. Throughout its history, the hospital has been making efforts to expand its range of services to cater to the needs of its constituents who live in General Santos City and some of its neighboring cities, municipalities, and provinces, but the hospital’s lack of a library suggests that establishing one could improve the hospital’s services. The researcher conducted a focus group discussion as a means to gather information from the respondents which are in the form of opinions answered from a set of questions assessing the feasibility of the establishment of the hospital. This was chosen to ensure the researcher is able to gather the most raw data possible, inviting the hospital’s department representatives and the certain officials from the General Santos City government.

Results indicate that the respondents, who represent certain departments of the hospital and the government, believe that establishing a library in the hospital is indeed feasible. The viewpoints collected from the discussion answered each question asked in the statement of the problem, giving a conclusion that the a library for the DJPRH might be established in the near future given that it passes all components that make a proposal feasible. The researcher recommends not just more feasibility studies related to establishing libraries in hospitals outside General Santos, but studies about hospital libraries in general.
Thesis
Keywords: Dr. Jorge P. Royeca Hospital; Medical libraries -- Philippines